THE DETERMINATION OF LANDFILL (TPA) ALTERNATIVE LOCATION IN WEST TULANG BAWANG DISTRICT OF LAMPUNG PROVINCE - Desy Renisita; Sunjoto Sunjoto; Sarto Sarto (Master in Systems Engineering, 2015)
West Tulang Bawang is one of the new regencies in Indonesia which was a new expanded area that continues to grow. It is followed by population growth rates resulting in increased volume of waste. The landfill (TPA) is an important component of any waste management system. A good waste has several characteristics. To ensure the appropriate selected land, a systematic process must be developed and followed.The study of the selection of the landfill (TPA) is aimed at finding feasible area as the location of the landfill, so that the allocation of the new landfill will be in accordance with local policies in regional spatial planning and meet the criteria of ISO No. 19-3241-1994. The role of Geographic Information System (GIS) in the management of solid waste is important because many aspects of planning and operations are highly dependent on the spatial data. The landfill selection process consists of three stages of filtering, i.e., the feasibility of the environment by utilizing Geographic Information System (GIS) to map the location of viable landfill, regional filtering phase based on the regional policy and the elimination filtering using SNI 19-3241-1994.The results of the study showed that with an estimated population in 2033 which is 330 807 people, the amount of waste that will go to the landfill through the 3R principle reached 309.36 m3 / day or 61.87 tons / day so that the area of the required land for the sanitary landfill pattern with a 20 year planning is 17.70 Ha. The alternative location was selected by with a priority level which is located on the Panaragan Jaya Utama of Central Tulang Bawang sub-district with a land of 99.68 hectares, Tulang Bawang village districts Panaragan Central with a land area of 136.26 ha and the Kagungan Ratu village of Tulang Bawang sub-district of 74 , 65 Ha.